Symptom Experience and Symptom Clusters of Thai Women with Breast Cancer Receiving Chemotherapy - Chongkham-ang, Supaporn; Wonghongkul, Tipaporn; Panuthai, Sirirat; Pinyokham, Nitaya; Miaskowski, Christine (Pacific Rim International Journal of Nursing Research, 2018)
Women with breast cancer experience multiple co-occurring symptoms and symptom clusters associated with chemotherapy. Understanding these symptom clusters will help to improve the effectiveness of symptom management. The purposes of this study were to explore symptom experience, symptom clusters, and to compare similarities and differences in symptom clusters based on severity and distress. Three hundred and twenty-two Thai women with breast cancer receiving chemotherapy were recruited from eight hospitals in Thailand. The instruments consisted of a Demographic and Clinical Data Form and the Thai-Memorial Symptom Assessment Scale. Data were analyzed using descriptive statistics and factor analysis. The five most common symptoms reported by these women were hair loss, lack of energy, lack of appetite, change in the way food tastes, and nausea. Lack of appetite was the most frequent symptom, and hair loss was the most severe and distressing symptom. Based on the analysis of severity and distress ratings, four symptom clusters were identified that were labeled emotional, gastrointestinal, image, and discomfort. The four symptom clusters based on severity or distress explained 49.49% and 54.51% of the variance in all of the symptoms, respectively. Similarity rates between the symptom clusters created using severity and distress ratings ranged from 33.33% to 100.00%. These findings suggest that symptom clusters are relatively similar regardless of the dimension evaluated. Nurses and other health care providers should assess these symptom clusters and provide appropriate symptom management interventions for these women.